Plerixafor and granulocyte‐colony‐stimulating factor for mobilization of hematopoietic stem cells for autologous transplantation in Chinese patients with non−Hodgkin's lymphoma: a randomized Phase 3 study. Issue 1 (13th December 2017) - Zhu, Jun; Huang, Huiqiang; Chen, Huan; Zhang, Xi; Li, Zengjun; Wu, Depei; Zhou, Daobin; Song, Yongping; Hu, Yu; Liang, Yingmin; Ren, Hanyun; Huang, He; et al.
Abstract : BACKGROUND: This Phase 3 randomized, double‐blind study evaluated the efficacy and safety of plerixafor plus granulocyte‐colony‐stimulating factor for the mobilization of hematopoietic stem cells in Chinese patients with non−Hodgkin's lymphoma. STUDY DESIGN AND METHODS: Adults (ages 18‐75 years) with non−Hodgkin's lymphoma in first or second complete or partial remission, without previous hematopoietic stem cell mobilization or autologous transplant, were included. Patients received granulocyte‐colony‐stimulating factor 10 µg/kg/day from Days 1 through 4 before they were randomized (1:1) to receive either plerixafor 0.24 mg/kg/day or placebo subcutaneously on Days 4 through 7 plus continued granulocyte‐colony‐stimulating factor on Days 5 through 8. Apheresis began on Day 5 and continued for no more than 4 days. The primary endpoint was collection of 5 × 10 6 CD34+ cells/kg or greater over no more than 4 days of apheresis. Other endpoints included the collection of 2 × 10 6 CD34+ cells/kg or greater and safety. RESULTS: Overall, 101 patients were enrolled, and 50 were randomized to each group. More patients in the plerixafor group achieved 5 × 10 6 CD34+ cells/kg or greater (62 vs. 20%; p < 0.0001) or 2 × 10 6 CD34+ cells/kg or greater (88 vs. 66%) and underwent transplantation (88 vs. 68%) compared with those in the placebo group. The most common plerixafor‐related adverse events were nausea (7.8%) and diarrhea (3.9%). CONCLUSION: Plerixafor plus granulocyte‐colony‐stimulating factor is superior to placebo plus granulocyte‐colony‐stimulating factor for the mobilization of CD34+ cells for autologous transplantation and is generally well tolerated in Chinese patients with non−Hodgkin's lymphoma.